(untitled) - Dimitrova, Birgitta Englund (Philadelphia, 2005)
This book addresses the complexities of the translation process. Informed by theoretical and methodological advances in translation studies, research on writing and the expertise paradigm, it explores translation as a text reproduction task. With triangulation of data from Russian-Swedish translation – think-aloud-methodology and computer logging of the writing process - it makes a cross-sectional comparison of subjects with different amounts of translation experience, highlighting crucial aspects of professional competence and expertise in translation. The book also elaborates a method for a combined product and process analysis, applying it to the study of one type of explicitation: increased cohesive explicitness of the target text. The results have implications for translation theory and pedagogy. This volume will be of interest to translation scholars and translator trainers, irrespective of language combination, as well as to specialists in Russian and Swedish. It will also appeal to researchers on expertise in other domains.
Keywords: Biên phiên dịch,Translating and interpreting